Black folk then and now : an essay in the history and sociology of the Negro race - Du Bois, W. E. B. (William Edward Burghardt), 1868-1963 (Du Bois, W. E. B. (William Edward Burghardt), 1868-1963. Works. 2007., 2007)
W.E.B. Du Bois was a public intellectual, sociologist, and activist on behalf of the African American community. He profoundly shaped black political culture in the United States through his founding role in the NAACP, as well as internationally through the Pan-African movement. Du Bois's sociological and historical research on African-American communities and culture broke ground in many areas, including the history of the post-Civil War Reconstruction period. Du Bois was also a prolific author of novels, autobiographical accounts, innumerable editorials and journalistic pieces, and several.